2011
DOI: 10.1007/s00128-011-0371-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Metals in the Edible Catfish Heteropneustes fossilis (Bloch) Exposed to Coal Mine Effluent Generated at Northern Coalfield Limited, Singrauli, India

Abstract: Metal accumulation in various tissues of Heteropneustes fossilis exposed to the effluent generated from an open cast coal mine was investigated. The contents of Fe, Mn, Cu, Zn, Ni, Pb, Cd and Cr in the effluent were above the permissible limits as suggested by the different pollution control agencies. Out of the eight metals investigated, accumulation (mg kg(-1) dry weight of tissue) of Fe was maximum in every tissues followed by liver (265.88 ± 49.89) > kidney (153.0 ± 65.85) > gills (50.66 ± 23.923) > brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In previous work, it has been shown that the effluent generated from the Dudhichua site, NCL, Singrauli contains metal (Fe, Mn, Zn, Ni, Cr, Cu, Cd, and Pb) concentrations above the safe limits .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, it has been shown that the effluent generated from the Dudhichua site, NCL, Singrauli contains metal (Fe, Mn, Zn, Ni, Cr, Cu, Cd, and Pb) concentrations above the safe limits .…”
Section: Resultsmentioning
confidence: 99%
“…Prior to death, several vital organ systems of CME exposed H. fossilis became progressively damaged as indicated by altered biochemical configuration (Tabs. [2][3][4][5][6]. Out of the seven tissues, reduction in glycogen content of muscles and brain was progressive throughout exposure periods (Tab.…”
Section: Biochemical Endpointsmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, fish are often used as sensitive bio-indicators of trace element pollution to evaluate the health of aquatic ecosystems (Dórea, 2008;Bharti and Banerjee, 2011;Al Sayegh Petkovšek et al, 2012). Heavy metals are concentrated at different levels in different organs of the body (Chi et al, 2007), and evaluation of these levels is considered important for understanding the health of an organism (Buggy and Tobin, 2008;Ayotunde et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of studies have focused on invertebrate species, several studies have described a range of potential sub-lethal impacts in fish, which are related to coal mine discharge. These include effects on survival (Scullion and Edwards, 1980;Mylliemngap and Ramanujam, 2012), community structure (Branson and Batch, 1971;Daniel et al, 2014), morphometrics Banerjee, 2013, 2014), metal uptake (Bharti and Banerjee, 2011;Arnold et al, 2014), genotoxicity (Benassi et al, 2006), reproduction (Rudolph et al, 2008), metabolism (Miller et al, 2009) and oxidative stress (Benassi et al, 2006). However, research pertaining to native Australian fish species has been extremely limited, particularly considering the national importance of the mining industry.…”
Section: Introductionmentioning
confidence: 97%